Alcoholic beverage consumption, quality of life and physical activity level in university students in the Physical Education course (Research, Society and Development, 2022)
The consumption of alcoholic beverages is an old custom and is present in the lives of young Brazilians today. Nowadays, alcohol has been a precursor of several diseases on the planet. In this sense, the objective of the present study was to verify the consumption of alcoholic beverages, as well as its association with the level of physical activity and the quality of life in students of the Physical Education course. A descriptive study was carried out with 26 university students regularly enrolled in the Physical Education course, with three questionnaires being applied: one that analyzes the subjective perception of quality of life (WHOQOL); another to assess alcohol consumption patterns (AUDIT), and, finally, one that assesses the level of physical activity (IPAQ). After data collection made by Google Forms®, these were analyzed. The results show that most students were classified in the “Low risk” zone (80.77%), and that 87.5% of them are considered physically active. In addition, no differences were found between the quality of life domains for students in the groups classified as “Low risk” or “Use of risk”. It is concluded that most of those evaluated were classified as active and Low risk of alcohol consumption. The consumption of alcoholic beverages did not influence the quality of life of the analyzed sample.